Ten Little Treasures of Game Theory and Ten Intuitive Contradictions - Goeree, Jacob K; Holt, Charles A (American Economic Review, 2001)
This paper reports laboratory data for games that are played only once. These games span the standard categories: static and dynamic games with complete and incomplete information. For each game, the treasure is a treatment in which behavior conforms nicely to predictions of the Nash equilibrium or relevant refinement. In each case, however, a change in the payoff structure produces a large inconsistency between theoretical predictions and observed behavior. These contradictions are generally consistent with simple intuition based on the interaction of payoff asymmetries and noisy introspection about others' decisions. (JEL C72, C92)